(untitled) (Interdisciplinary Research in Education, 2023)
Integrating values in curricular and pedagogical activities has become a pressing need to produce responsible social citizens with good hearts and great minds. To cultivate these traits, values need to be reflected in and be the part of school curriculum and pedagogy. In this context, school practices play a pivotal role to make values a part of everyday activity. This study attempts to examine such practices in public, private, and traditional/religious schools in Nepal. Schools were selected purposively by visiting their online profiles. Information was collected from twenty school heads via a semi-structured interview, school visits, and classroom observations. The study found that private and public schools have initiated teaching/integrating values through a range of curricular structures and pedagogical practices like happiness curriculum, IB curriculum, education in human values curriculum, living school curriculum, culture-based [sanskar] curriculum, progressive learning approach, and innovative pedagogical models. It was also found that schools have designed their internal curricula within the spirit of the national curriculum framework to integrate soft skills and values in regular lessons. Traditional/religious schools have been found blending general courses and certain religious values like Gurukul schools- teaching Vedic values, Madrasa schools- teaching Islamic values, Gonpas/Monasteries- teaching Buddhist/Tibetan values, and St. Xavier schools- teaching Jesuit values. Having these noticeable initiatives in values education in Nepal, effective endorsement from the policy level is required for visible impacts.